Self-assembled Human Serum Protein-based Core-shell Nanoparticles to inhibit key oncogenic signalling in Drug-Resistant Leukemia - Archana Payickattu Retnakumary; Lekshmi G Kumar; Neeraj Sidharthan; Pavithran Keechilat; Giridharan L. Malarvizhi; Prasanna L Hanumanthu; Madhavan V Thampi; Deepthy Menon; Krishnakumar Menon; Shantikumar V Nair; Manzoor Koyakutty (Precision Nanomedicine)
Simultaneous inhibition of multiple oncogenic signaling pathways is crucial for managing refractory cancers. This study introduces two unique core-shell nanoparticle (CS-NP) systems crafted from natural proteins that simultaneously target two crucial oncogenic pathways in refractory chronic myeloid leukemia (CML). Molecular analysis of approximately 14 refractory CML patients identified resistance to the standard treatment drug, imatinib, attributed to the overex-pression of the STAT5-transferrin pathway alongside the classic BCR-ABL fusion gene. To address this, we developed two dual-drug-loaded core-shell nanoparticles: (a) CS-NP1: Protamine sulfate nanocores carrying BCR-ABL siRNA and an albumin shell loaded with the STAT5 in-hibitor sorafenib, denoted as (PS-siRNA)-(Tf-Soraf) CS-NP; (b) CS-NP2: features a second-generation BCR-ABL inhibitor, dasatinib, in the albumin nanocore, and sorafenib in the transferrin nanoshell, labeled as (nAlb-Dasa)-(Tf-Soraf). We hypothesized that these dual-drug-loaded CS-NPs would effectively target both BCR-ABL and STAT5 pathways, with the transferrin nanoshell aiding in precise delivery to refractory CML cells overexpressing TfR1 due to STAT5 activity. Initial evaluations in drug resistant CML cell lines and patient-derived cells demonstrated significant cytotoxicity. Remarkably, even patients with BCR-ABL oncogene mutations displayed over 95% cytotoxicity with the CS-NPs. Furthermore, in vivo testing on a human xeno-graft model with a BCR-ABL+/+/STAT5+/+/TfR+/+ phenotype showcased a strong anti-tumor response. These results underscore the potential of a molecular-diagnosis-based rational design approach for protein-protein core-shell nanoparticles to simultaneously inhibit multiple oncogenic pathways, thereby overcoming resistance to targeted molecular therapies.